Kualitas Pelayanan dan Kepuasan Masyarakat Terhadap Pelayanan Kantor Desa - Eka Nuraini; Ibrais Shalahuddin Eriyanto (MAMEN: Jurnal Manajemen, 2023)
The quality of service prioritizes the interests of the community as service recipients, but the services provided are sometimes less than optimal, causing many complaints from the public. The purpose of this study is to describe the quality of service and community satisfaction. This research is a descriptive quantitative research. Data obtained by questionnaire technique. The research subjects were 30 people who had received services at the Aik Ketekok Village Office. Based on the data obtained, it is known that the percentage of service quality variable is 67.35% in the percentage range of 61% -80% with good criteria. The variable percentage of community satisfaction is 71.22% in the percentage range of 61% -80% with good criteria. Judging from the percentage figures for these two variables, it shows that the role of service quality in increasing community satisfaction is not maximized even though these two variables are qualitatively included as good criteria. Therefore, the quality of service can be improved by re-informing the explanations conveyed to the people being served, making promises on time for service, maintaining the cleanliness and tidiness of the service room. In addition, employees must apply minimum service standards, ensuring that service requirements match the type of service. The ability of employees to provide services also needs to be improved by means of self-development in accordance with developments in science and technology.